Understanding Psychosocial Factors Influencing Subjective Well-Being in Perinatal Mothers: A Systematic Literature Review - Nadya Novia Rahman; Ayunda Ramadhani; Aulia Ramdani (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
The perinatal period represents a complex and vulnerable developmental transition characterized by substantial biological, psychological, social, and environmental changes. Maternal subjective well-being during this phase extends beyond the absence of mental disorders and encompasses life satisfaction, positive affect, perceived competence, and meaningful engagement in the maternal role. This study aimed to systematically synthesize psychosocial determinants influencing subjective well-being among perinatal mothers through a systematic literature review approach. Inclusion criteria comprised peer-reviewed English-language journal articles published between 2010 and 2026 that examined intrapersonal, relational, socioeconomic, and environmental determinants among pregnant and postpartum women. Following the PRISMA framework, 17 studies met the eligibility criteria and were included in the final analysis. The findings indicate that emotional regulation, maternal self-efficacy, risk perception, childbirth experience, sleep quality, social support, stigma, socioeconomic conditions, and environmental stressors are key interacting determinants shaping maternal subjective well-being. Furthermore, psychosocial interventions such as psychoeducation, cognitive-emotional regulation-based programs, and digital support platforms demonstrate promising potential in enhancing maternal resilience. The results underscore the importance of adopting an ecological framework integrating individual, relational, and structural dimensions to comprehensively understand maternal well-being. This review shifts the focus from a pathology-oriented perspective toward a strength-based and well-being-centered paradigm and provides important implications for maternal mental health policy development and preventive intervention strategies.Periode perinatal merupakan fase transisi perkembangan yang kompleks dan rentan, ditandai oleh perubahan biologis, psikologis, sosial, dan lingkungan yang signifikan. Kesejahteraan subjektif ibu pada masa ini tidak hanya mencerminkan ketiadaan gangguan mental, tetapi juga mencakup kepuasan hidup, afek positif, rasa kompetensi, serta makna dalam menjalankan peran keibuan. Penelitian ini bertujuan untuk mensintesis secara sistematis faktor-faktor psikososial yang memengaruhi kesejahteraan subjektif ibu perinatal melalui pendekatan systematic literature review. Kriteria inklusi meliputi artikel jurnal peer-reviewed berbahasa Inggris yang diterbitkan antara 2010–2026 dan meneliti determinan intrapersonal, relasional, sosial ekonomi, serta lingkungan terhadap kesejahteraan subjektif ibu hamil dan postpartum. Proses seleksi mengikuti kerangka PRISMA dan menghasilkan 17 artikel yang memenuhi kriteria. Hasil tinjauan menunjukkan bahwa regulasi emosi, self-efficacy maternal, persepsi risiko, pengalaman persalinan, kualitas tidur, dukungan sosial, stigma, kondisi sosial ekonomi, serta stresor lingkungan merupakan determinan utama yang saling berinteraksi dalam membentuk kesejahteraan subjektif. Selain itu, intervensi psikososial seperti psikoedukasi, cognitive-emotional regulation, dan dukungan berbasis digital terbukti berpotensi meningkatkan resiliensi maternal. Temuan ini menegaskan pentingnya pendekatan ekologi yang mengintegrasikan faktor individual, relasional, dan struktural dalam memahami kesejahteraan ibu perinatal. Studi ini berkontribusi dengan menggeser paradigma dari pendekatan berbasis patologi menuju perspektif berbasis kekuatan dan kesejahteraan, serta memberikan implikasi bagi pengembangan kebijakan dan strategi promotif-preventif kesehatan mental maternal.